Relatório de Estágio Profissionalizante realizado no Futebol Clube do Porto - Marta Areias da Costa Maia (2017)
This Internship Report integrates the curricular plan of final year of the 2nd Cycle in Sports Management at the Faculty of Sport of the University of Porto.The internship training took place in Futebol Clube do Porto, in PortoEstádio company, integrating the Planning Department, and it was aimed to develop skills and knowledge in the area of Sports Management, applied to the modalities of Handball, Basketball and Rink Hockey.The purpose of this document is to describe the experiences related to the internship period and analyse the entire learning process.The completion of this internship made possible to understand the fundamental process of planning, organization and operation of sports events and the cooperation and active participation in the events developed by Futebol Clube do Porto.The accomplishment of the internship also allowed the understanding of the importance of the manager in sports' reality, in particular in the whole process of managing these events.The end of this period revealed the importance of this internship, not only for personal development, but also for the acquisition and consolidation of competence for the future professional practice.